RENTE EKONOMI PERDAGANGAN SATWA LIAR DAN TERPINGGIRKANNYA KESEJAHTERAAN HEWAN - Anggalih Bayu Muh. Kamim (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
The state has made various efforts to protect the lives of wild animals from the risk of illegal trade. Various regulations starting from the CITES convention have been ratified and followed up with various other regulations. Although, a series of efforts have been made to protect wild animals from extinction, but animal trade continues. This study explores how the commodification of wild animals carried out by the state since its habitat causes the life of animals threatened. This research is a desk study conducted by tracking secondary data from environmental organization monitoring reports, government reports, journal articles, online media related to the topic being studied. The results of the study show that the forest territorial initiation process carried out by the state through species control, unilateral determination of forest area boundaries and formal control through various institutions and regulations actually causes wild animals and their habitats to be threatened by economic exploitation efforts. Residents around the territorial forest that were affected by territoriality were forced to become hunters to make a living. The state apparatus also cannot be separated in taking advantage of opportunities to be involved in hunting wild animals. Illegal hunting is a supplier for the trade in wild animals involving various modes of sale. The lives of wild animals have truly been threatened by making them commodities. The food chain has changed by making economic rents the main predator for wildlife.